The Mediating Role of Hope in the Relationship Between Peer Social Support and Resilience among Indonesian Generation Z - Fildzah Hanifati; Ni'matuzahroh Ni'matuzahroh (Universitas Islam Tribakti Lirboyo Kediri, 2026)
Generation Z (Gen Z) faces substantial psychosocial pressures during higher education and early career transitions, underscoring the importance of resilience for positive adaptation. However, research examining the psychological mechanism through which peer social support contributes to resilience among Indonesian Gen Z remains limited. This study aimed to examine the mediating role of hope in the relationship between peer social support and resilience among Indonesian Gen Z. Employing a quantitative correlational design, the study involved 102 Gen Z participants aged 18–28 selected via purposive sampling. Data were collected using the 25-item Connor-Davidson Resilience Scale (CD-RISC-25), the Social Provisions Scale (SPS), and the Adult Hope Scale (AHS), and were analyzed using Hayes’ PROCESS macro (Model 4). Results indicated that peer social support significantly predicted resilience, while hope partially mediated this relationship between peer social support and resilience (β= .389, 95% CI [.194, .630]). The model accounts for 56.1% of the variance in resilience (R2= .561). These findings underscore that Gen Z resilience is shaped by the interaction between external interpersonal resources and internal psychological resources, with hope functioning as the psychological mechanism linking peer social support to resilience. The findings highlight the importance of developing interventions that strengthen peer support networks while fostering hope to enhance resilience during academic and early-career transitions.